Algorithmic Constitutionality: New Challenges for Constitutional Law in The Era of Artificial Intelligence - Vidi Galenso Syarief; Marjan Miharja; Gunawan Nachrawi; Yusuf Gunawan (Greenation International Journal of Law and Social Sciences, 2026)
The development of artificial intelligence (Artificial Intelligence/AI) technology has encouraged the use of algorithms in various aspects of government administration, including administrative decision-making, public service delivery, and the management of state data. The presence of algorithms as decision-making instruments raises new issues in constitutional law, particularly in relation to the principles of constitutionality, constitutional supremacy, the protection of human rights, and the general principles of good governance. This article aims to analyze the position of algorithms from the perspective of constitutional law and to examine the constitutional challenges arising from the use of algorithms in governmental practice in the era of artificial intelligence. The research method employed is normative legal research using a statute approach, a conceptual approach, and a comparative approach. The legal materials used include statutory regulations and legal literature relevant to the development of digital technology and algorithm-based governance. The findings indicate that the use of algorithms in government has the potential to improve the efficiency, accuracy, and transparency of public services; however, it also poses serious challenges to the principle of constitutionality, such as the risk of algorithmic discrimination, lack of transparency (black box algorithm), and the potential violation of the right to personal data protection and the right to procedural justice. Therefore, it is necessary to strengthen the legal framework and constitutional oversight mechanisms for the use of algorithms in government administration, including the establishment of specific regulations, algorithmic accountability standards, and judicial oversight that is adaptive to technological developments.